Ready to bully automated vehicles on public roads?. (March 2020) - Liu, Peng; Du, Yong; Wang, Lin; Da Young, Ju
Highlights: We designed an eleven-item bullying intention questionnaire. Participants in China and South Korea had a greater intention to bully AVs than to bully other human drivers. Chinese (vs. Korean) participants reported a greater intention to drive aggressively. Male (vs. female) participants reported a greater intention to drive aggressively. Younger (vs. older) participants reported a greater intention to drive aggressively. Abstract: Automated vehicles (AVs), the wide adoption of which is expected to improve traffic safety significantly, are penetrating our roads. The AVs that are testing on public roads have been bullied by human road users. We are not sure whether the bullying incidents are isolated or will be common in the future. In a cross-national survey ( N = 998 drivers in China and South Korea), we developed an eleven-item bullying intention questionnaire. We assumed and confirmed that, overall, participants had a greater intention to bully machine drivers than to bully other human drivers. Compared to the Korean participants, the Chinese participants reported a greater intention to drive aggressively. The correlations of their intention to bully AVs with their attitude toward AVs and with risk-benefit perception of AVs were weak. Male participants (vs. female participants) and younger participants (vs. older participants) reported a greater intention to drive aggressively. Drivers' aggressive behaviors toward AVs might be common in the future, which might increase traffic risk and hinder the implementation of this technology.